Gas Bubbles from Biodegradable Magnesium Implants Convey Mechanical Cues and Promote Immune Cell Stimulation - Heithem Ben Amara; Jincy Philip; Omar Omar; Peter Thomsen (Advanced Science)
Abstract In ever‐increasing numbers, patients are treated with biodegradable magnesium implants. While gas bubbles frequently arise in soft tissue overlying magnesium implants, their biological implications remain uncertain. This study investigates how bubble accumulation and evolution across various biological lengths and time scales influence adjacent tissue and cell behavior in rats. Bubbles accumulate in tissues around magnesium during initial postimplantation days, then fully resorb. Alterations in tissue and cell geometry around bubbles coincide with accumulation of cells, many with macrophage phenotypes, and increased expression of the mechanosensitive ion‐channel Piezo1. Using spatially resolved transcriptomics, strong proinflammatory pathway activation is revealed near bubbles with marked expression of the proliferative macrophage marker secreted phosphoprotein 1 (Spp1). Spatial transcriptomics also reveals strong enrichment of cytoskeletal rearrangement genes, demonstrating that cells respond to mechanical cues from bubbles. Notably, both time and bubble–implant distance strongly influence the cellular response. Over time, as bubbles are located farther from the implant, regenerative processes decline, and inflammation predominates. These findings suggest that bubbles from magnesium implant degradation create an intricate local response influencing tissue healing through inflammatory and mechanical pathways. This study underscores the need for magnesium implants with controlled gas release and meticulous monitoring of bubble evolution in patients.